From Chalkboard to Cliks: Digital Media Preferences and Learning Barriers in Distance Organic Chemistry Education - Inas Sausan; Ayu Fahimah Diniyah Wathi; Faizal Akhmad Adi Masbukhin (Universitas Sebelas Maret, 2026)
This study investigates students’ preferences for digital instructional media and the main learning barriers in the Organic Chemistry 3 course at Universitas Terbuka (UT), Indonesia’s leading open and distance learning institution. Using a descriptive quantitative approach, data were collected from 25 students and alumni through an online questionnaire and analyzed descriptively. The results indicate that interactive simulations (39%) and instructional videos (38%) were the preferred media, highlighting students’ strong preference for dynamic, visualized learning experiences. Major barriers included difficulty in visualizing reaction mechanisms (68%) and insufficient prerequisite mastery (52%), revealing cognitive and structural challenges in learning complex organic chemistry concepts remotely. The analysis further showed a gap between high pedagogical needs (70–85%) and moderate contextual barriers (45–55%), reflecting students’ prioritization of instructional quality despite infrastructural limitations. The study concludes that effective distance chemistry instruction must combine strong pedagogical design, technological accessibility, and continuous learner support to foster deep conceptual understanding. Recommendations include integrating step-by-step guided videos, interactive simulations, adaptive scaffolding, and accessible media formats aligned with students’ needs and learning contexts.